CEO power and characteristics on firm performance in Indonesian state-owned enterprisesh - Ayi Ahadiat; Mahrinasari MS; Usep Syaipudin; Fajrin Satria Dwi Kesumah (Contemporary Economics, 2023)
Financial performance is an important indicator in a company in measuring the level of viability of the company. This study aims to analyze the effect of CEO power (proxied by CEO ownership), and characteristics (CEO educational background and work experience) on firm performance as proxied by ROA with the moderating variable of the percentage of the number of independent commissioners. The population in this study were all companies officially listed on the Indonesia Stock Exchange in 2015-2019. Then the sampling system used purposive sampling and obtained 16 state-owned companies listed on the Indonesia Stock Exchange. The results show that in model 1, CEO ownership variable has no effect on company performance, while the educational background variable has a significant negative effect and work experience variable has a significant positive effect on firm performance. In model 2, only the educational background variable has a significant effect, and the moderating variable does not strengthen the relationship between all independent variables on the company's financial performance.
Keywords: G23; G3; G30; M1; M12; 330; firm performance; state-owned enterprises; CEO power; CEO characteristics